2010
DOI: 10.4049/jimmunol.1000889
|View full text |Cite
|
Sign up to set email alerts
|

Drug Antigenicity, Immunogenicity, and Costimulatory Signaling: Evidence for Formation of a Functional Antigen through Immune Cell Metabolism

Abstract: Recognition of drugs by immune cells is usually explained by the hapten model, which states that endogenous metabolites bind irreversibly to protein to stimulate immune cells. Synthetic metabolites interact directly with protein generating antigenic determinants for T-cells; however, experimental evidence relating intracellular metabolism in immune cells and the generation of physiologically relevant antigens to functional immune responses is lacking. The aim of this study was to develop an integrated approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 61 publications
1
44
0
1
Order By: Relevance
“…Exposure of keratinocytes to SMX promoted the release of proinflammatory cytokines and increased expression of heat shock protein 70 (Khan et al, 2007). We have shown that (1) SMX metabolism and protein adduct formation above a threshold stimulates cell death and (2) drugmetabolite modified necrotic cells provide a powerful activation signal to dendritic cells (Naisbitt et al, 2002;Elsheikh et al, 2010). Thus, metabolism of SMX might indirectly activate cutaneous dendritic cells and support the presentation of skin-derived drug-protein adducts.…”
Section: The Antigenicity and Immunogenicity Of Drugs That Acquirementioning
confidence: 99%
See 2 more Smart Citations
“…Exposure of keratinocytes to SMX promoted the release of proinflammatory cytokines and increased expression of heat shock protein 70 (Khan et al, 2007). We have shown that (1) SMX metabolism and protein adduct formation above a threshold stimulates cell death and (2) drugmetabolite modified necrotic cells provide a powerful activation signal to dendritic cells (Naisbitt et al, 2002;Elsheikh et al, 2010). Thus, metabolism of SMX might indirectly activate cutaneous dendritic cells and support the presentation of skin-derived drug-protein adducts.…”
Section: The Antigenicity and Immunogenicity Of Drugs That Acquirementioning
confidence: 99%
“…However, oxidation of SMX hydroxylamine occurs spontaneously, generating nitroso SMX, which has been shown to modify selective cysteine residues expressed on both cellular and extracellular protein (Naisbitt et al, 1999(Naisbitt et al, , 2002Manchanda et al, 2002;Summan and Cribb, 2002;Callan et al, 2009;Eyanagi et al, 2012 ). Modification of cell surface proteins on immune cells occurs rapidly; protein conjugates are then internalized via caveolae-dependent endocytosis (Manchanda et al, 2002;Elsheikh et al, 2010).…”
Section: The Antigenicity and Immunogenicity Of Drugs That Acquirementioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that drugs activate T cells by covalent modification of protein generating novel antigenic determinants (2,3,(7)(8)(9). However, the paucity of studies that define the chemistry of drug-protein binding in patients has severely restricted mechanistic studies that relate the chemistry of Ag formation to immune function.…”
mentioning
confidence: 99%
“…The liver is quantitatively the primary site of SMX bioactivation, though metabolism has been shown to occur in other organs including the skin, kidney, lung and cells of the immune system [49,50]. Furthermore, SMX metabolism by dendritic cells enhances their state of activation [51,52]. We have previously shown that SMX-HA leads to the haptenation of cellular proteins [53] including HIV-1 infected Jurkat T cells and Jurkat T cells expressing the different deletion forms of Tat (data not shown).…”
Section: Resultsmentioning
confidence: 99%